2020
DOI: 10.1177/0276236620913008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prototype-Based Scale for Assessing Saudade

Abstract: Saudade is a psychological experience resulting from the absence of significant others or familiar places. Four studies were conducted in view of creating a measure of saudade derived from previous prototype analyses. Data from four samples were collected: two samples of Portuguese undergraduate students, one sample of Portuguese adults, and one sample of Portuguese adolescents. Through exploratory and confirmatory factor analyses, a three-factor latent structure of saudade was identified: Missing Close Others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Hence, it is not surprising that feelings of saudade are particularly present during adolescence. In fact, it has been shown that the experience of saudade was more frequent among adolescents than among adults (Neto & Mullet, 2020b). Our expectations were that PSS scores would display a single-factor structure and good internal consistency.…”
Section: Studymentioning
confidence: 83%
See 4 more Smart Citations
“…Hence, it is not surprising that feelings of saudade are particularly present during adolescence. In fact, it has been shown that the experience of saudade was more frequent among adolescents than among adults (Neto & Mullet, 2020b). Our expectations were that PSS scores would display a single-factor structure and good internal consistency.…”
Section: Studymentioning
confidence: 83%
“…Saudade is deeply rooted in the daily lives of the Portuguese. Neto and Mullet (2020b) found that about 40% of participants in their samples (Portuguese adolescents, students or migrant adults living abroad) experienced saudade often or very often.…”
Section: Saudadementioning
confidence: 96%
See 3 more Smart Citations